Albo crosses the line: the Labor win in the 2022 Australian federal election. Issue 5 (3rd September 2022) - McDougall, Derek
ABSTRACT: Labor has won a slim majority in the House of Representatives in the 2022 Australian federal election. Labor pursued a 'small target' strategy, focusing on economic issues. Labor and the Coalition combined won only about two-thirds of the primary vote. The new government faces a deteriorating economy and significant energy issues. However, Labor will make climate action a higher priority, also giving attention to such matters as a constitutionally enshrined indigenous 'voice' to parliament and a federal integrity commission. Internationally, Labor claims to be more effective than the Coalition, with some prospect of improved relations with China.